Peran Kelompok Kerja Guru Pendidikan Agama Islam dalam Pengembangan Kompetensi Profesional Guru Sekolah Dasar - Asmira Wati; Harvius Harvius (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The professional competence of Islamic Education (PAI) teachers plays a decisive role in determining the quality of learning at the elementary school level. In practice, many teachers still encounter challenges in mastering subject content, developing systematic teaching materials, applying innovative learning strategies, and integrating educational technology into classroom activities. These conditions indicate the need for structured professional development efforts through collaborative forums. This study aims to analyze the role of the Islamic Education Teachers Working Group (KKG PAI) in maximizing the professional competence of PAI teachers in public elementary schools in Panti District, Pasaman Regency, and to identify the supporting and inhibiting factors influencing its implementation. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving the KKG supervisor, the head of KKG PAI, and member teachers. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that KKG PAI functions as a strategic platform for collaborative lesson planning, subject-matter enrichment, peer reflection, and technology-based instructional training. Supporting factors include strong teacher commitment and collaborative culture, while limitations in facilities and technological disparities remain challenges. Strengthening the sustainability and management of KKG programs is essential to enhance teachers’ professional competence and improve the overall quality of Islamic education learning.